Akuisisi Bukti Digital Pada Aplikasi Michat di Smartphone Menggunakan Metode National Institute of Standards and Technology (NIST) - Soni Soni; Regiolina Hayami; Muhammad Hamadi (Universitas Muhammadiyah Riau, 2022)
The development of technology in the world of mobile devices is growing. However, these developments have a detrimental impact, one of which is cybercrime. Cybercrime is a crime that uses information technology. One of the smart phone technologies which includes cases of cybercrime that are often found in Indonesia include online prostitution of minors. This is done by utilizing social media, namely Michat as a medium of communication. The “chat with nearby users” feature by uploading a status that can be connected to the surrounding area within a certain radius and after being connected, the actor and his potential customer will negotiate and transact with each other until they finally meet. To eliminate digital evidence in the form of conversations in messages, usually perpetrators will delete the history of messages that produce data that can be used as evidence and perpetrators who can avoid legal traps, which are ultimately online. prostitution will be rampant. For online prostitution activities, it is necessary to carry out mobile forensics to find evidence which is then useful to be given to the authorities. This research uses the National Institute of Standards and Technology (NIST) method.